2008
DOI: 10.1016/j.ultsonch.2007.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrostatic pressure and sound amplitude on the ultrasound induced dispersion and de-agglomeration of nanoparticles

Abstract: In most applications, nanoparticles are required to be in a well-dispersed state prior to commercialisation. Conventional technology for dispersing particles into liquids, however, usually is not sufficient, since the nanoparticles tend to form very strong agglomerates requiring extremely high specific energy inputs in order to overcome the adhesive forces. Besides conventional systems as stirred media mills, ultrasound is one means to de-agglomerate nanoparticles in aqueous dispersions. In spite of several pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(67 citation statements)
references
References 8 publications
3
61
0
3
Order By: Relevance
“…Besides, the cavitation threshold increases linearly with the static pressure, thus the acoustic pressure amplitude required to reach the cavitation threshold also increases [17]. Yasui et al [18] showed the optimal static pressure which maximizes the acoustic energy increases as the acoustic amplitude increases or viscosity of liquid decreases, which qualitatively agrees with Sauter et al [19].…”
Section: Effect Of Pressure On Sonication Efficacysupporting
confidence: 66%
“…Besides, the cavitation threshold increases linearly with the static pressure, thus the acoustic pressure amplitude required to reach the cavitation threshold also increases [17]. Yasui et al [18] showed the optimal static pressure which maximizes the acoustic energy increases as the acoustic amplitude increases or viscosity of liquid decreases, which qualitatively agrees with Sauter et al [19].…”
Section: Effect Of Pressure On Sonication Efficacysupporting
confidence: 66%
“…One of the first papers published using this technique investigated the effects of high intensity ultrasound on micron-sized inorganic solids with powders of 60 -90 µm diameter being reduced to 5-10 µm in diameter after a few minutes of ultrasonic irradiation [12]. A number of nanomaterials that have been the subject of recent dispersion investigations include goethite [13,14] , silica [15][16][17][18][19] , haematite 3 [20], barium titanate [21], zinc oxide [22], carbon black [23], silver [23], alumina [24][25][26] and carbon nanotubes [27]. In many of these studies, high intensity ultrasonic processing was found to de-agglomerate and decrease the size of the starting materials.…”
Section: Introductionmentioning
confidence: 99%
“…Other process devices used by previous researchers include the sawtooth impeller (Xie et al, 2007), batch rotor-stator (Xie et al, 2007;Pacek et al, 2007), high pressure devices Sauter and Schuchmann, 2012), stirred bead mills (Kowalski et al, 2008, Schilde et al, 2011 and ultrasonicators (Sauter et al, 2006(Sauter et al, , 2008. Some of the studies included numerical modelling to develop both an understanding of the flows within process devices which are not accessible for measurements and also models describing the deagglomeration process (Baldyga et al, 2006(Baldyga et al, , 2007(Baldyga et al, , 2008(Baldyga et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%